2018
DOI: 10.15673/fst.v12i2.945
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Grape Powders on the Rheological Properties of Dough and Characteristics of the Quality of Butter Biscuits

Abstract: The effect of grape powders on the rheological properties of dough and the indicators of butter biscuits quality have been investigated. Butter biscuits were cooked with the addition of powdered grape seeds and grape skins from the grape pomace obtained in the southern regions of Ukraine. The grape powders were added to the dough in an amount of 15.0% of the weight of the wheat flour. It has been shown that the presence of powdered grape skins increases the dough’s effective viscosity by 3.9 times, of powdered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Grape juice pomace presented lower tannin, anthocyanin, and flavonoid than wine pomace, but the total phenols values were close to (Iuga & Mironeasa, 2020). The polyphenol content depends on the growing zone, climatic conditions, grape variety, and processing conditions during pomace drying (Brykova et al, 2018). The major component in juice pomaces was epicatechin (Gülcü et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Grape juice pomace presented lower tannin, anthocyanin, and flavonoid than wine pomace, but the total phenols values were close to (Iuga & Mironeasa, 2020). The polyphenol content depends on the growing zone, climatic conditions, grape variety, and processing conditions during pomace drying (Brykova et al, 2018). The major component in juice pomaces was epicatechin (Gülcü et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of cookies volume and thickness with grape peels addition is related to the high fiber content, which reduces the gas retention capacity (Deng et al, 2011;Kuchtová et al, 2018;Walker et al, 2014). Grape peels or seeds were added to butter biscuits to slightly increase the specific volume and to increase the stability and wetting ability as compared to the control, as Brykova et al (2018) showed. On contrary, a decrease of butter biscuits volume with the grape seed flour addition level increase was reported by Samohvalova et al (2016), acceptable results being obtained for replacements up to 15%.…”
Section: Effects Of Grape Byproducts Addition On the Physical Charactmentioning
confidence: 94%
“…The same trend of the wet gluten content was obtained by Aghamirzaei et al (2015) for wheat flour containing different levels of grape seeds powder. According to the results presented by Brykova, Samohvalova, Grevtseva, Kasabova, and Grygorenko (2018), butter biscuits dough viscosity and plastic viscosity increased when grape peels or seeds powders were added, the modulus of instantaneous springiness and the elasticity modulus decreasing compared to the control.…”
Section: Dough Rheology and Wheat Flour Properties As Influenced By Gmentioning
confidence: 95%
See 1 more Smart Citation